The English as a Foreign Language / Lingua Franca Debate: Sensitising Teachers of English as a Foreign Language Towards Teaching English as a Lingua Franca - Gillian Mansfield; Franca Poppi (Profile: Issues in Teachers' Professional Development)
The function of English as a lingua franca for communication needs rethinking in the teaching of English as a foreign language classroom as a consequence of globalisation. The present contribution is an empirical study carried out in an Italian university environment which aims to show how teachers should take on board awareness raising activities in the recognition of other varieties of English which, albeit not exploited as benchmarks for language testing and certification, must nevertheless boast a relevant place in the global scenario. This can be achieved in practical terms by interrogating an expressly made corpus of Chinese English news texts and carrying out simple concordance activities.